Penggunaan E-wallet pada Generasi Milenial dengan Pendekatan UTAUT pada Mahasiswa Perbankan Syariah UIN Mahmud Yunus Batusangkar - Gampito, Gampito; Rahma, Faiza Nabila; Candra, Revi; Hasibuan, Abdul Nasser (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The purpose of this study was to analyze the interest in using E-walet among UIN Mahmud Yunus Batusangkar students using the Unified Theory Of Acceptance Use Of Technology (UTAUT) approach. The research method used is descriptive quantitative. The study population was 357 students of the Sharia Banking study program with a sample of 78 people calculated using the slovin formula. Data collection techniques using questionnaires. The data analysis technique uses multiple linear regression. The results showed that performance expectancy, social influence, and facilitating conditions partially influenced the interest in using e-wallets for students of the Islamic Banking Study Program, UIN Mahmud Yunus Batusangkar. While effort expectancy has no effect on interest in using e-wallets.┬á Simultaneously performance expectancy, effort expectancy, social influence, and facilitating conditions affect the interest in using e-wallets among students. The contribution of performance expectancy, effort expectancy, social influence, and facilitating conditions variables to influence interest is 68.3%.